Isolation of a Seawater Tolerant Leptospira spp. from a Southern Right Whale (Eubalaena australis) - Grune Loffler, Sylvia; Rago, María Virginia; Martinez, Mara Leila; Uhart, Marcela María; Florin Christensen, Mónica; Romero, Graciela; Brihuega, Bibiana (PLOS ONE)
Leptospirosis is the most widespread zoonotic disease in the world. It is caused by pathogenic spirochetes of the genus Leptospira spp. and is maintained in nature through chronic renal infection of carrier animals. Rodents and other small mammals are the main reservoirs. Information on leptospirosis in marine mammals is scarce; however, cases of leptospirosis have been documented in pinniped populations from the Pacific coast of North America from southern California to British Columbia. We report the isolation of a Leptospira spp. strain, here named Manara, from a kidney sample obtained from a Southern Right Whale (Eubalaena australis) calf, which stranded dead in Playa Manara, Península Valdés, Argentina. This strain showed motility and morphology typical of the genus Leptospira spp. under dark-field microscopy; and grew in Ellinghausen-McCullough-Johnson-Harris (EMJH) medium and Fletcher medium after 90 days of incubation at 28°C. Considering the source of this bacterium, we tested its ability to grow in Fletcher medium diluted with seawater at different percentages (1%, 3%, 5%, 7% and 10% v/v). Bacterial growth was detected 48 h after inoculation of Fletcher medium supplemented with 5% sea water, demonstrating the halophilic nature of the strain Manara. Phylogenetic analysis of 16S rRNA gene sequences placed this novel strain within the radiation of the pathogenic species of the genus Leptospira spp., with sequence similarities within the range 97-100%, and closely related to L. interrogans. Two different PCR protocols targeting genus-specific pathogenic genes (G1-G2, B64I-B64II and LigB) gave positive results, which indicates that the strain Manara is likely pathogenic. Further studies are needed to confirm this possibility as well as determine its serogroup. These results could modify our understanding of the epidemiology of this zoonosis. Until now, the resistance and ability to grow in seawater for long periods of time had been proven for the strain Muggia of L. biflexa, a saprophytic species. To the ...